Dialogic reflection for professional development through conversations on a social networking site. Issue 1 (2nd January 2018) - Ab Rashid, Radzuwan
Abstract: This article provides insights into how teachers benefited from their engagement in teaching-related conversations on Facebook timelines. The main data generated from participant observation and semi-structured interviews involving 34 English language teachers were analyzed using thematic and discourse analysis approaches. The analysis reveals that the teachers' supportive conversations on the timelines revolve around troublesome experiences encountered in school which serve as a trigger for the teachers to engage in dialogic reflection, which enables them to have a better interpretation of their professional lives. The findings from this study point towards the need for reconceptualization of 'teacher professional development' as an opportunity for the construction of a collective and satisfying interpretation of themselves-in-the-world, where teachers work together to make sense of both mundane reality and stressful teaching-related events through the co-construction of social support.